Processamento de vistas ortogonais para modelagem 3D automatizada com Python - Hayashi, Lucas Magario (2023)
Through the study of fundamental concepts related to the processing of orthogonal views, edge detection algorithms, and 3D modeling, an incipient project was developed for an automated system in Python, capable of producing 3D models from the processing of orthogonal views with the help of the software Blender. The objective of the developed algorithm is to detect edges of orthogonal views, treat, optimize, and store data, in addition to using computer graphics software to model and visualize the solid. The results obtained confirmed the viability and effectiveness of the system for simple solids, becoming an efficient solution for modeling 3D objects, making the process faster, easier, and with a lower error rate. In addition, this project also aims to facilitate the understanding and visualization of technical drawing concepts for academic environments.